IMPROVING THE METHODOLOGY FOR DEVELOPING STUDENTS' KINESTHETIC INTELLIGENCE BASED ON ACADEMIC SUBJECTS - Umirzoqova Surayyo Xudoyberdiyevna (Modern American Journals, 2025)
This article explores the essence of students' kinesthetic intelligence and its role within the theory of multiple intelligences. It provides a detailed analysis of methods for developing this type of intelligence through specialized academic subjects. Active learning tools and interactive teaching strategies are examined as effective means for engaging students, enhancing their learning processes, and fostering creativity and reflective thinking. Moreover, the article presents practice-based methodological suggestions supported by results from experimental studies and modern pedagogical technologies.
Keywords: Kinesthetic intelligence, movement-based learning, academic disciplines, interactive methodology, practical exercises, modern technologies, student-centered approach, pedagogical innovation